PARTISIPASI MASYARAKAT DESA DALAM PENYUSUNAN PERATURAN DESA - Kadar Pamuji (MIH Unsoed, 2017)
Mandate to promote participation of the villagers stated in Article 18 paragraph (7) and Article 18B (2) of the Constitution of the Republic of Indonesia Year 1945, one of which is to encourage initiative, movement, and the participation of village communities to the development potential and Assets Village in order commonweal.The substance of the Village Act of 2014 contains a lot of opportunities for people to participate in governance and rural development. Article 3 explicitly states that the village setting one of them are basically the principle of participation that is actively involved in an activity, and then in Article 4 letter d. states that the setting of the village aims to encourage initiative, movement, and the participation of the village community to the development potential and assets for the welfare of the village together, even in Article 68 paragraph (2) letter e. that society is obliged to participate in various activities in the village.Establishment of Village Regulation (Perdes) participatory must reflect the shared commitment between Kepala Desa (village head), Village Consultative Body (BPD) and villagers. To make a good Perdes conducted prior study of potential village and constraints, so Perdes made totally based on needs and not wants.In the process of its formation, Village Regulations require community participation so that the final outcome of Village Regulation can meet the legal enforceability aspect and can be implemented according to the purpose of its formation. Public participation in this case can be input and discordant thoughts in the formulation of the substance of Village Regulations setting. Law or legislation will be able to be effective if it meets three power sell well as the philosophical, juridical, and sociological. Besides, it also must pay attention to the effectiveness / economic power and political behavior.In essence Preparation of Village Regulation is not an activity that is carried out solely to fulfill the duties of Head of Village and BPD, but really to solve the problem and provide benefits to rural communities so respected by the communities themselves.Keywords: Participation, Communities, Village Regulations